2018
DOI: 10.1016/j.jcma.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hypoxic and mesopic environments on visual acuity, contrast sensitivity and accommodation in subjects with LASIK surgery and aircrew candidate

Abstract: There was no significant difference of visual acuity between the two groups regarding hypoxic and mesopic environment, but reduced contrast sensitivity was significant in LASIK group as compared to those of the control group. Accommodation was significantly lowered in LASIK group, compared with control group, in hypoxic environment. Whether postoperative visual performance after LASIK in aircrew during flying duty is safe might need further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…It is confirmed that near corrective refraction was associated with refractive error, but we found no significant correlation between SER with CSF. Previous studies reported the potential relationship of accommodation and CSF [33,34], and near corrective refraction reflects the accommodation ability to some extent, which we speculated may be a potential factor for this finding. The results of our study suggested that an exceptionally high corrective spectacle prescription for presbyopia caused some deficits in CSF.…”
Section: Discussionmentioning
confidence: 55%
“…It is confirmed that near corrective refraction was associated with refractive error, but we found no significant correlation between SER with CSF. Previous studies reported the potential relationship of accommodation and CSF [33,34], and near corrective refraction reflects the accommodation ability to some extent, which we speculated may be a potential factor for this finding. The results of our study suggested that an exceptionally high corrective spectacle prescription for presbyopia caused some deficits in CSF.…”
Section: Discussionmentioning
confidence: 55%
“…В ранее проведенных исследованиях сообщалось о нарушениях аккомодационной и (или) бинокулярной функции глаза, связанных с послеоперационной анизометропией и роговичными осложнениями [6], однако в нашей работе данные факторы являлись критериями исключения пациентов из исследования. Более четкое и сопоставимое с представленными результатами настоящего исследования заключение было сформулировано в работах авторов, которые утверждают, что проведение ЛАСИК не оказывает существенного влияния на аккомодацию, при этом выявленные послеоперационные нарушения были диагностированы в рамках предоперационного обследования [24][25][26].…”
Section: результатыunclassified